14PValidation of the optimum timing of assessment of tumour infiltrating lymphocytes during preoperative chemotherapy for breast cancer. (24th November 2019) - Kashiwagi, S; Asano, Y; Kouhashi, R; Ishihara, S; Tauchi, Y; Morisaki, T; Noda, S; Takashima, T; Onoda, N; Hirakawa, K; Ohira, M
Abstract: Background: Host tumor microenvironment (TME) assessment is considered to play an important role in the prognostic and therapeutic predictions of breast cancer treatment. No consensus has been reached regarding evaluation methods despite reports of the utilization of tumor-infiltrating lymphocytes (TILs) for tumor immune microenvironment (TIME) monitoring. While the International Working Group recommends a tumor stromal evaluation, the timing of TIME assessment has not yet been established. Here, we focused on the assessment time and verified clinical predictions of neoadjuvant chemotherapy (NAC) effects using TILs. Methods: Two hundred thirty-nine patients were treated with neoadjuvant chemotherapy (NAC). During the period from diagnostic needle biopsy to NAC initiation for breast cancer, the optimal evaluation timing was examined using a receiver operating characteristic (ROC) curve analysis. Results: The prognostic analysis revealed that both disease-free survival (DFS) and overall survival (OS) were significantly prolonged in the short-term group (118 patients) relative to the long-term group (121 patients) (p = 0.020, p = 0.010, log-rank). A significant correlation between TILs and pathological complete response (pCR) was only observed in the short-term group (p = 0.033). Prognostic analysis revealed that in the short-term group, the high TIL group had a significantly better survival prognosis relative to the low TIL group (DFS: p = 0.001, OS: p = 0.021, log-rank). TILs were also found to be a significant factor affecting DFS in the univariate analysis (p = 0.004, hazard ratio = 0.115), as well as an independent factor affecting the DFS in a multivariate analysis (p = 0.008, hazard ratio = 0.130). Conclusions: The timing of TIL assessment during NAC for breast cancer may be more sensitive index in the short term (≤35 days). Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.